Enhancement on 5G Cellular System's Framework & Architecture to Support Mission Critical Communications Encompassing Multimedia Data and Voice Communications - Norehan, Yahya (2021)
Public Safety Networks (PSN) provide mission critical communications (MCC) to agencies providing emergency services like police, fire and ambulance. Most PSN Network Operators, including PMR A, utilize TETRA PSN systems for their voice communications, and cellular LTE for their broadband needs. To meet these purposes, they operate dual PSN hybrid network (LTE/TETRA), which are cost prohibitive and operationally inefficient. PMR A aspires to have a single PSN network using Cellular system that meets their MCC requirements provided that the technical gaps on the service offerings can be adequately addressed. PMR A characterized ‘easy to use push to talk services with unlimited users for Groupcalls’ as the most critical technical gap. To realize the single PSN MCC network aspiration, the opportunities made available from cutting edge mobile solutions delivered over telecommunication’s new 5G Cellular Network Architecture will need to be fully exploited. Pursuant to this, the research objectives and methodology, were aimed at addressing gaps by providing 5G design recommendations to meet specific communication needs of MCC for multiple agencies over a single PSN network. The objectives and methodology are summarized as follows: Objective 1: Identify MCPTT and MCC Performance Gap. Qualitative study and 5G Lab experiments were conducted to validate the 5G architecture technical gaps. Objective 2: Develop 5G commercial network enhancements to support MCC. Qualitative study was used to develop and validate the 5G PSN architecture. Objective 3: Improve the 5G PSN design using SDN to support multiple agency use. Qualitative study was used to develop and validate the 5G PSN architecture. The Theoretical Framework of this research was adapted from industry framework comprising of 5G Cellular system network elements (NE), inclusive of 5G Core, 5G Access Network, 5G QoS, 5G Applications and 5G Security. ‘The Open Group Architecture Framework’ ii(TOGAF) approach was adopted for this qualitative research with 3GPP used as the standards benchmark. The most crucial research finding was, the 5G PSN network architecture support for ‘simple to use MCPTT with unlimited users for Group Calls’, was reflected as the deciding factor for migration from TETRA to 5G PSN network. To bridge this gap, and all the technical gaps acknowledged by industry experts, the research recommendations included enhancements to 5G NEs via implementation of ‘5G PSN Developmental Framework & Architecture’ that capitalizes on 3GPP’s ‘Group Communication System’, ‘evolved Multimedia Broadcast Multicast System’ and ‘User & Bearer Prioritization Tool’ architectures, incorporated with Network Slicing and Network Function Virtualization, delivered over Software Define Networks With this novelty, the research concluded that, migration towards a single 5G PSN deployment by PMR A, could be accelerated to meet evolving MCC needs.